An Analysis of Lexical Relations in the Luca’s Movie Script by Mike Jones and Jesse Andrews - Linda Fitri Ibrahim; Evi Mariana (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2026)
This research aims to (1) describe the types of lexical relations in the Luca movie script by Mike Jones and Jesse Andrews and; (2) describe the most dominant lexical relations in the Luca Movie script by Mike Jones and Jesse Andrews. The methodology used was qualitative-descriptive; the data source is the Luca movie script by Mike Jones and Jesse Andrews. For the result of research, the researcher describes as follow: (1) there were eight types of lexical relations in the Luca movie script by Mike Jones and Jesse Andrews as follows: homonym (20), polysemy (2), synonym (113), antonym (57), hyponym (11), meronym (2), member-collection (17) and portion-mass (1), and; (2) the most dominant types of lexical relations in Luca movie script by Mike Jones and Jesse Andrews was synonym (113).